(6x+1)+(-7x+7)=

Simple and best practice solution for (6x+1)+(-7x+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+1)+(-7x+7)= equation:


Simplifying
(6x + 1) + (-7x + 7) = 0

Reorder the terms:
(1 + 6x) + (-7x + 7) = 0

Remove parenthesis around (1 + 6x)
1 + 6x + (-7x + 7) = 0

Reorder the terms:
1 + 6x + (7 + -7x) = 0

Remove parenthesis around (7 + -7x)
1 + 6x + 7 + -7x = 0

Reorder the terms:
1 + 7 + 6x + -7x = 0

Combine like terms: 1 + 7 = 8
8 + 6x + -7x = 0

Combine like terms: 6x + -7x = -1x
8 + -1x = 0

Solving
8 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -1x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -1x = 0 + -8
-1x = 0 + -8

Combine like terms: 0 + -8 = -8
-1x = -8

Divide each side by '-1'.
x = 8

Simplifying
x = 8

See similar equations:

| n^2+3n+4=0 | | 75t^10+35y^7= | | 2=4*2-3 | | 14x+21y=91 | | 14x+91y=91 | | -0.4=8/x | | -[10x-(3x+3)]=-6-[4(3x-4)-3x] | | 2=-3*2+1 | | -38+8x=-8(5-x) | | 3x-4y=105x+7y=3 | | y=-9/4*1-9 | | 5y^2+37y+42=0 | | y-9/4*1-9 | | 1/6(10x-2)=3 | | y=9/4*1-9 | | x/4-117/4x=-1 | | -2=-2+4 | | -2(m+35)=8m | | y=9/4*0-9 | | y=2.1x+1.4 | | 20r^2-5= | | 6(1)-2y=22 | | 4w-4=4 | | 2=10*2+3 | | 9x^2+42x+49=784 | | -4(m-5)=-6m | | f(x)=12x+14 | | 48r^2-3= | | 0=7*0-5 | | 72/21 | | 0=7*-5 | | 5x-6=5(x+1) |

Equations solver categories